Danish Vernacular – Nationalism and History Shaping Education - Hyams, Inger Berling (ARCC Conference Repository, 2014)
Despite the number of internationally successful Danish architects like Jacobsen, Utzon and in recent years Ingels just to name a few, Danish architecture has always leaned greatly on international architectural history and theory. This is only natural for a small nation. However, since the beginning of Danish architecture as a professional discipline, there has also been a formation of a certain Danish vernacular. This paper explores how the teaching of and interest in Danish historical buildings could have marked the education of Danish architecture students. Through analysis of the drawings of influential teachers in the Danish school, particularly Nyrop, this development is tracked. This descriptive and analytic work concludes in a perspective on the backdrop of Martin Heidegger's differentiation between Historie and Geschichte – how history was used in the curriculum and what sort of impact the teachers had on their students. Such a perspectivedoes not just inform us of past practices but could inspire to new ones.